Verbal art, verbal sign, verbal time - Jakobson, Roman, 1896-1982 (University of Minnesota Press, 1985)
The work of Roman Jakobson has long been recognized as central to debates in linguistics and literary theory. This book makes Jakobson's ideas, previously collected only in a monumental, seven-volume edition of his selected writings, readily available for the first time. It brings together eleven essays on topics of crucial importance to poetics and linguistics.